2005
DOI: 10.1097/01.ju.0000148949.72314.d7
|View full text |Cite
|
Sign up to set email alerts
|

A DECREASE IN 1 H NUCLEAR MAGNETIC RESONANCE SPECTROSCOPICALLY DETERMINED CITRATE IN HUMAN SEMINAL FLUID ACCOMPANIES THE DEVELOPMENT OF PROSTATE ADENOCARCINOMA

Abstract: To our knowledge this study is the first to use high resolution NMR of semen to diagnose prostate cancer. Given the known effects of adenocarcinoma on prostate metabolism, the study indicates that high resolution H NMR can be used to measure citrate in seminal fluid, potentially providing a new, rapid, noninvasive screening method.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
34
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(36 citation statements)
references
References 16 publications
2
34
0
Order By: Relevance
“…In fact, citrate is the unique prostatic metabolite in seminal plasma investigated by high resolution NMR analysis as a marker to diagnose prostatic cancer [Averna et al 2005] or in men with spinal cord injury [Alexandrino et al 2009]. None of these conditions were detected in our patient population.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…In fact, citrate is the unique prostatic metabolite in seminal plasma investigated by high resolution NMR analysis as a marker to diagnose prostatic cancer [Averna et al 2005] or in men with spinal cord injury [Alexandrino et al 2009]. None of these conditions were detected in our patient population.…”
Section: Resultsmentioning
confidence: 97%
“…Before the NMR analysis, the samples were lyophilized and resuspended in deuterium oxide. Figure 1 shows the NMR proton spectrum of a human seminal plasma sample in D 2 O solution acquired at 600 MHz and 298 K. The assignment reported in detail in Table 1 was obtained by bidimensional NMR spectra (data not shown) according to previous papers [Gupta et al, 2011a,b;Averna et al 2005;Gupta et al 2013;Lynch et al 1994;Patel et al 1999;Seaglen et al 1995]. The enlarged signals at 7.18, 6.92, 6.89, and 6.75 ppm, marked with an asterisk in Figure 1, in the region of aromatic protons of phenylalanine, tyrosine, and histidine, show a characteristic line width broadening of proton resonances.…”
Section: Resultsmentioning
confidence: 99%
“…Several other metabolites are currently being screened for diagnostic imaging in preclinical models 20, 20a . Metabolite levels of citrate 21,22,23,24,25,26,27 , choline 28,29 , glutamate 30 , taurine 30 , and sarcosine 31 in body fluids, such as urine and serum, as well as in tissue biopsies have been correlated with PCa progression and the change in levels of these metabolites, when analyzed globally, could be a potential strategy for distinguishing indolent from aggressive disease.…”
Section: Introductionmentioning
confidence: 99%
“…Our long history of applications of NMR to prostate cancer diagnosis 2,25,26,[33][34][35][36][37] suggested that we turn to this area for a candidate cell-surface epitope to discriminate between cancer cells and normal, non-malignant cells. Research on prostate cancer-specific cell markers 25,[27][28][29] led to the identification of PSMA, the folate receptor, as a cell-surface protein that is highly-overexpressed on prostate tumors.…”
Section: Specific Binding Of Anti-psma-conjugated Spions To Psma-posimentioning
confidence: 99%